A Review of the Evidence for the Provision of the Routine Scale and Polish for the Prevention of Periodontal Disease. (2nd March 2021) - Birt, Rachel; Healy, Claire M; MacCarthy, Denise; Winning, Lewis
Abstract : The routine scale and polish is the most commonly performed treatment procedure in general dental practice. With a large proportion of state dental health expenditure in the UK and Ireland being used to provide 'routine scale and polish' treatments, it is necessary to establish the true value of this treatment for patients. In this narrative review, we discuss the available evidence regarding provision of the routine scale and polish. Based on the available studies, there is little evidence to support the use of the routine scale and polish alone for the prevention of periodontal disease. CPD/Clinical Relevance: This paper evaluates the evidence surrounding the routine provision of scaling and polishing for the prevention of gingivitis and periodontitis.